Amino Assets: How Amino Acids Support Immunity - Kelly, Beth; Pearce, Erika L. (Cell metabolism, 2020)
Amino acids are fundamental building blocks supporting life. Their role in protein synthesis is well defined, but they contribute to a host of other intracellular metabolic pathways, including ATP generation, nucleotide synthesis, and redox balance, to support cellular and organismal function. Immune cells critically depend on such pathways to acquire energy and biomass and to reprogram their metabolism upon activation to support growth, proliferation, and effector functions. Amino acid metabolism plays a key role in this metabolic rewiring, and it supports various immune cell functions beyond increased protein synthesis. Here, we review the mechanisms by which amino acid metabolism promotes immune cell function, and how these processes could be targeted to improve immunity in pathological conditions. In this Review, Kelly and Pearce highlight the role of amino acids in immune cell function. They outline that beyond driving protein synthesis, amino acids support immunity by modulating immune cell energy metabolism, redox balance, epigenetic modification, nucleotide synthesis, autophagy, and post-translational protein modification.